Farmers’ preferences for climate-smart agriculture: An assessment in the Indo-Gangetic plain - Taneja, Garima; Pal, Barun Deb; Joshi, Pramod Kumar; Aggarwal, Pramod K.; Tyagi, Narendra K. (International Food Policy Research Institute, 2014)
This study was undertaken to assess farmers’ preferences and willingness to pay (WTP) for various climate-smart interventions in the Indo-Gangetic Plain. The research outputs will be helpful in integrating farmers’ choices with government programs in the selected regions. The Indo-Gangetic Plain (IGP) was selected because it is highly vulnerable to climate change, which may adversely affect the sustainability of the rice-wheat production system and the food security of the region. Climate-smart agriculture (CSA) can mitigate the negative impacts of climate change and improve the efficiency of the rice-wheat-based production system. CSA requires a complete package of practices to achieve the desired objectives, but adoption is largely dependent on farmers’ preferences and their capacity and WTP.